2014 IEEE International Conference on Communications (ICC) 2014
DOI: 10.1109/icc.2014.6884121
|View full text |Cite
|
Sign up to set email alerts
|

Norm-based joint transmit/receive antenna selection aided and two-tier channel estimation assisted STSK systems

Abstract: Abstract-We propose a simple yet effective norm-based joint transmit and receive antenna selection (NBJTRAS) assisted and two-tier channel estimation (TTCE) aided space-time shift keying (STSK) system, which is capable of significantly outperforming the conventional STSK system, while efficiently utilising available radio frequency (RF) chains. Specifically, the NBJTRAS carries out antenna selection based on the channel estimation (CE) generated using a low-complexity training based least square channel estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…As a matter of fact, the antenna selection (AS) approach can be tailored to alleviate the requirements of RF chains in massive MU-MIMO systems. AS aims to select the optimal or near-optimal channel subset associated with better channel condition from the whole channel set, and thus to provide a low-complexity strategy to reduce the number of RF chains utilised in the transmitter and/or receiver, while remaining the performance gain of massive MIMO systems [1]. Generally, the AS criteria can be divided into two categories: norm-based AS (NBAS) and capacity-based AS (CBAS) [1,2].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…As a matter of fact, the antenna selection (AS) approach can be tailored to alleviate the requirements of RF chains in massive MU-MIMO systems. AS aims to select the optimal or near-optimal channel subset associated with better channel condition from the whole channel set, and thus to provide a low-complexity strategy to reduce the number of RF chains utilised in the transmitter and/or receiver, while remaining the performance gain of massive MIMO systems [1]. Generally, the AS criteria can be divided into two categories: norm-based AS (NBAS) and capacity-based AS (CBAS) [1,2].…”
Section: Literature Reviewmentioning
confidence: 99%
“…AS aims to select the optimal or near-optimal channel subset associated with better channel condition from the whole channel set, and thus to provide a low-complexity strategy to reduce the number of RF chains utilised in the transmitter and/or receiver, while remaining the performance gain of massive MIMO systems [1]. Generally, the AS criteria can be divided into two categories: norm-based AS (NBAS) and capacity-based AS (CBAS) [1,2]. The NBAS schemes are addressed in [1][2][3][4], which aim at selecting antenna subset that are capable of maximising the equivalent signal-to-noise ratio (SNR) of the systems with relatively low computational complexity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Reference [10] proposed a joint RxAS and power allocation scheme for 5G massive MIMO uplink communication, which is capable of promoting energy conservation then improving the good quality of service (QoS). Furthermore, [2], [11] proposed a two-tier channel estimation (TTCE) aided NBAS by jointly selecting Tx and Rx antennas, which showed that by employing joint Tx and Rx AS, the system's performance may be improved, while retaining low hardware costs and computational complexity. Additionally, [12] compared the performance of joint Tx and Rx AS with TxAS and RxAS, which concluded that the diversity order of JTRAS was significantly reduced in the presence of feedback errors.…”
Section: Introductionmentioning
confidence: 99%